Detección de Falla en Máquina de Inducción Mediante Análisis Multiresolución - San Juan-Urrutia, E; Canete-Arratia, L; Adasme-Soto, P; Viveros-Llabres, A; Cordero-Leiva, S (Institute of Electrical and Electronics Engineers Inc., 2023)
In this paper, a short-circuit fault detection is carried out in an induction machine using the Wavelet Transform. For its development, a multi-resolution analysis is performed on the machine s current in healthy and faulty states. Subsequently, the energy deviation technique is applied to each detail of the multiresolution analysis, allowing for a comparison of both results. Finally, it is confirmed that short-circuit faults can be detected through multi-resolution analysis by comparing the resulting energy deviation curves with the short-circuit curve. © 2023 IEEE.